2016
DOI: 10.1007/s10549-016-3894-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a prior diagnosis of DCIS on survival from invasive breast cancer

Abstract: A diagnosis of invasive breast cancer after DCIS can be described as a new primary cancer or as a local invasive recurrence. It is of interest to determine if, among women with early-stage breast cancer, a past history of DCIS influences survival. We retrieved the records of 306,249 women diagnosed with stage I or stage II breast cancer between 2004 and 2012, in the surveillance, epidemiology, and end results registries database, of whom 5395 had a previous diagnosis of DCIS. For each patient, we extracted inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The IBCs mainly harbored favorable clinicopathologic characteristics, with the majority of cases being the ductal subtype, stage I (pT1 N0), SBR grade I-II, ER positive, and HER2 negative. These data are in accordance with the previous studies by Romero [8], Silverstein [7], and Sopik [9], where patients with ILR after prior ipsilateral DCIS mainly had same good prognosis features (stage I tumors, SBR grade II, and positive ER status).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The IBCs mainly harbored favorable clinicopathologic characteristics, with the majority of cases being the ductal subtype, stage I (pT1 N0), SBR grade I-II, ER positive, and HER2 negative. These data are in accordance with the previous studies by Romero [8], Silverstein [7], and Sopik [9], where patients with ILR after prior ipsilateral DCIS mainly had same good prognosis features (stage I tumors, SBR grade II, and positive ER status).…”
Section: Discussionsupporting
confidence: 93%
“…Although outcomes in patients with non-invasive recurrence are excellent, data are sparse regarding outcomes after invasive recurrence [ 8 ], and existing data in the literature are conflicting concerning the prognosis of this entity per se. Indeed, some studies have reported that patients with invasive recurrence after primary DCIS have a particularly poor prognosis [ 8 ], while others have reported no difference in prognosis for women who experience invasive breast cancer (IBC), with or without prior DCIS [ 9 ]. Therefore, the question of invasive ipsilateral relapse management after DCIS remains unresolved, especially regarding the specific need for additional adjuvant systemic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The IBCs mainly harbored favorable clinicopathologic characteristics, with the majority of cases being the ductal subtype, stage I (pT1 N0), SBR grade I-II, ER positive and HER2 These data are in accordance with previous studies by Romero (8), Silverstein (7) and Sopik (9), where patients with ILR after prior ipsilateral DCIS mainly had same good prognosis features (stage I tumors, SBR grade II and positive ER status).…”
Section: Discussionsupporting
confidence: 90%
“…From the starting point of DCIS, risk factors which lead from progression of DCIS to invasive cancer include young age, high grade, and positive surgical margins [ 52 ]. From the point of view of the invasive cancer, the most important factor which predicts a prior diagnosis of DCIS is calendar year [ 53 ]. If we surmise correctly, breast cancers with and without a documented prior history of DCIS should carry a similar prognosis.…”
Section: Part 4: Are Primary Invasive Breast Cancers and Local Invasimentioning
confidence: 99%